Design of a wireless battery charger for cellular phone: article - Ibrahim, Mohd Basri Faris; Mohd Subri, Mohd Nor Safwan; Mohammad Nawawi Seroji, Mohammad Nawawi (2012)
This paper presents a new circuit for charging of the lithium-ion battery for a Cellular phone using wireless. The primary circuit was forward resonant converter being set up as the charger unit with the different shape and structure winding coil as compared to the secondary circuit with simple circuit, which is adopted as a wireless energy transfer device. The energy power transfer between these primary and secondary circuit is verified from the experiment result. The concept of inductive power transfer applied. The analysis of the primary side of circuit with is performed. A simple circuit for secondary side for battery charging is presented and the analysis is presented.